2014
DOI: 10.1017/s0266467414000613
|View full text |Cite
|
Sign up to set email alerts
|

Afromontane small mammals do not follow the hump-shaped rule: altitudinal variation in the Soutpansberg Mountains, South Africa

Abstract: Abstract:Altitudinal transects of biodiversity are important to understanding macro-ecological patterns. Hump-shaped altitudinal profiles in species richness are a common pattern in terrestrial small-mammal communities studied previously mostly in New World mountain ranges. Based on capture–mark–recapture live-trapping conducted over four seasons (four nights per session) along an altitudinal transect from 1000 to 1747 m asl on the southern slopes of the Soutpansberg Mountains of northern South Africa, we reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…This diversity compares favourably with studies reviewing the diversity of terrestrial small mammals (Taylor et al 2015) and bats (Schoeman et al 2013; Taylor et al 2013; Cooper-Bohannon 2016; Herkt et al 2016) in African highlands generally. However, the estimate of terrestrial small mammal richness is probably grossly under-estimated as a GBIF search of central Angola yielded 42 species, compared with our list of 13 species of shrews and rodents based on captures.…”
Section: Discussionsupporting
confidence: 55%
“…This diversity compares favourably with studies reviewing the diversity of terrestrial small mammals (Taylor et al 2015) and bats (Schoeman et al 2013; Taylor et al 2013; Cooper-Bohannon 2016; Herkt et al 2016) in African highlands generally. However, the estimate of terrestrial small mammal richness is probably grossly under-estimated as a GBIF search of central Angola yielded 42 species, compared with our list of 13 species of shrews and rodents based on captures.…”
Section: Discussionsupporting
confidence: 55%
“…The model domain of each aspect was bound by the altitudinal range of each study area (McCain 2005). We applied simple linear regression to test the correlation between empirical and predicted values (Taylor et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The study of Presley et al (2012) found that the metacommunity structure along an altitudinal gradient differs between bats, rodents and birds. While altitude seems to influence how the metacommunities are structured, bat communities are overlapping whereas groups of birds replace each other along the gradient, even more so do rodents (Taylor et al 2015). It is suggested that bird and rodent communities are structured according to the microhabitat they are specialized on, whereas bat community structure might be influenced more by the temperature, productivity and food, that particular species tolerate.…”
Section: Complementarity and Community Compositionmentioning
confidence: 99%
“…A revision of the Otomys irroratus species complex resolved two species restricted to the grassland (Otomys auratus) and fynbos (O. irroratus sensu stricto) biomes of South Africa (Taylor et al 2009, Engelbrecht et al 2011). Taylor et al 2009, 2011, Engelbrecht et al 2011, predicted range changes due to climate change under the A2 emission scenario (from Taylor et al 2015Taylor et al , 2016 and changes in the IUCN Red List status with different regional (Friedmann andDaly 2004, Child et al 2016) The two values listed for predicted % range changes refer to values calculated assuming (first value) and not assuming (second value) dispersal. Abbreviations as follow: N/A, not assessed; LC, least concern; DD, data deficient; VU, vulnerable; EN, endangered; CR, critically endangered.…”
Section: Conservation Implications Of Revised Taxonomiesmentioning
confidence: 99%